Succession of bacterial and fungal communities within biofilms of a chlorinated drinking water distribution system. (15th September 2018) - Douterelo, I.; Fish, K.E.; Boxall, J.B.
Abstract: Understanding the temporal dynamics of multi-species biofilms in Drinking Water Distribution Systems (DWDS) is essential to ensure safe, high quality water reaches consumers after it passes through these high surface area reactors. This research studied the succession characteristics of fungal and bacterial communities under controlled environmental conditions fully representative of operational DWDS. Microbial communities were observed to increase in complexity after one month of biofilm development but they did not reach stability after three months. Changes in cell numbers were faster at the start of biofilm formation and tended to decrease over time, despite the continuing changes in bacterial community composition. Fungal diversity was markedly less than bacterial diversity and had a lag in responding to temporal dynamics. A core-mixed community of bacteria including Pseudomonas, Massillia and Sphingomonas and the fungi Acremonium and Neocosmopora were present constantly and consistently in the biofilms over time and conditions studied. Monitoring and managing biofilms and such ubiquitous core microbial communities are key control strategies to ensuring the delivery of safe drinking water via the current ageing DWDS infrastructure. Graphical abstract: Image 1 Highlights: Succession of multi-species biofilms was studied under representative conditions. A core fungal-bacterial community was observed continuously over time. Bacteria responded rapidly while fungi had a lag in responding to biofilm dynamics. Core microorganisms are a potential tool to develop new control strategies.